Expression of functional granulocyte colony-stimulating factor receptors on human B-lymphocytic leukemia cells. - Handa, A; Kashimura, T; Takeuchi, S; Yamamoto, A; Murohashi, I; Bessho, M; Hirashima, K (2000)
We analyzed the expression of cell surface antigens and granulocyte colony-stimulating factor (G-CSF) receptors using flow cytometry, the expression of G-CSF mRNA receptor, using reverse transcription (RT)-PCR, and tested the effect of G-CSF on leukemia colony formation. A total of 14 lymphocytic leukemia patients were examined, seven with acute lymphocytic leukemia (ALL), two with adult T-cell leukemia (ATL), two with B-chronic lymphocytic leukemia (CLL), two with chronic myelocytic leukemia in lymphoid blastic crisis (CML-LBC), and one with plasma cell leukemia (PCL). The presence of G-CSF receptors was demonstrated in 4/14 (29%) patients, two with ALL, one with CLL, and one with CML-LBC, and was associated with stimulation of leukemia clonogenic cell growth by G-CSF. In addition, all four positive leukemia cell types expressed typical B-cell antigens. Our results indicated that G-CSF receptors are expressed on some portion of B-lymphoid leukemia and that their receptors are functional as growth stimulators.